ANALISIS TINGKAT KERAGAMAN PENGUKURAN VOLUME KAYU BULAT OLEH TENAGA TEKNIS PENGELOLAAN HUTAN PRODUKSI LESTARI (GANIS-PHPL) PADA APLIKASI SI-PUHH ONLINE - Isak W Silooy; G Mardiatmoko; Rohny S Maail (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
Therefore this study aims to analyze the level of diversity in the measurement of volume of logs in the field between researchers and Technical Personnel for Sustainable Production Forest Management (GANIS-PHPL) inputted in the SI-PUHH Online application. The method used is a quantitative method by developing models mathematical (calculations), which are related to the measurement of logs. The results showed that the Technical Personnel for Sustainable Production Forest Management (GANIS-PHPL) owned by PT. Gema Hutani Lestari is not careful in carrying out its duties and authorities in measuring the correctness of the volume of logs, because there has been an excess volume tolerance of 5.97% of the set tolerance limit of 5%, giving rise to an element of state losses. Thus the performance and role of GANIS-PHPL is deemed necessary for guidance and control related to its duties and authority in terms of measuring and testing the volume of logs, so that the calculation of non-tax state revenue (PNBP) reaches the desired target.